Early specialization in formative basketball: A machine learning analysis of shooting patterns in U14 and professional players - Contreras-García, J. M.; Courel-Ibáñez, J.; Piñar-López, M. I.; Ibáñez, S. J. (Journal of Sports Sciences, 2024)
Growing evidence supports that early sport specialization in children and adolescents may compromise long-term athlete development and high-performance acquisition. This study aimed to determine the presence of specialised shooting roles in formative men`s basketball players compared to professionals. Data from shot charts of U14 and professional basketball players during the 2020-21 and 2021-22 seasons were retrieved. Shooting zones were classified by machine learning and clustering analyses. Shooting patterns were defined as extreme field goal attempts (FGA%) from a particular shooting zone. Players who exhibited an outlier shooting pattern were considered specialists. U14 basketball players described singular shooting patterns that largely differed from professionals` requirements (p < 0.001, ES = 0.51). U14 players lacked shooting versatility (2.3% vs. 36.3%) and 3-point shooting ability (1.8 vs. 17.2%). In contrast, the professional competition was characterised by having either versatile players without specialisation (62.7%) or one-zone specialist shooters accumulating most of their %FGA in one court zone (38%). These findings suggested that increasing shooting versatility or becoming a one-zone specialist shooter could significantly impact the development and progression of young basketball players in the long term. Current formative basketball training approaches should be revised accordingly to enhance shooting skills and promote the development of polyvalent players.